THE FORMATION OF THE CREATIVITY OF STUDENTS DURING THE PERIOD OF PEDAGOGICAL PRACTICE - Alieva Ayshe Edemovna (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
From the pedagogical point of view, the article reveals the place and potential of pedagogical practice in the formation of creativity among bachelor students, the factors of the development of creativity. Also, some interpretations of the concept of creativity are given and analyzed. The components of the development of creativity among bachelors in the process of teaching practice are shown.